Intestinal microbiota of broilers submitted to feeding restriction and its relationship to hepatic metabolism and fat mass: Fast-growing strain - Lunedo, Raquel [UNESP]; Furlan, Luiz R. [UNESP]; Fernandez-Alarcon, Miguel F. [UNESP]; Squassoni, Gustavo H. [UNESP]; Campos, Daniel M. B.; Perondi, Dani [UNESP]; Macari, Marcos [UNESP] (Wiley, 2019)
The present study was conducted to verify how feed restriction affects gut microbiota and gene hepatic expression in broiler chickens and how these variables are related to body weight gain. For the experiment, 21-d-old Cobb500TM birds were distributed in a completely randomized experimental design with three treatments: T1. Control (ad libitum—3.176 Mcal/kg ME—metabolizable energy—and 19% CP—crude protein); T2. Energetic restriction (2.224 Mcal/kg ME and 19% CP) from 22 to 42 days with consumption equivalent to control; T3. Quantitative restriction (70% restriction, i.e., restricted broilers ingested only 30% of the quantity consumed by the control group—3.176 Mcal/kg ME and 19% CP) for 7 days, followed by refeeding ad libitum from 28 to 42 days. Ileum and caecum microbiota collections were made at 21, 28 and 42 days of age. Hepatic tissue was collected at 28 and 42 days old for relative gene expression analyses. At 43-d-old, body composition was quantified by DXA (Dual-energy X-ray Absorptiometry). Both feed restriction programmes decreased Lactobacillus and increased Enterococcus and Enterobacteriaceae counts. No differences were found in the refeeding period. Energetic restriction induced the expression of CPT1-A (Carnitine palmitoyltransferase 1A) gene, and decreased body fat mass. Quantitative feed restriction increased lipogenic and decreased lipolytic gene expression. In the refeeding period, CPT1-A gene expression was induced, without changing the broilers body composition. Positive associations were found between BWG (Body Weight Gain) and Lactobacillus and Clostridium cluster IV groups, and negatively associations with Enterobacteriaceae and Enterococcus bacterial groups. In conclusion, differences found in microbiota were similar between the two feed restriction programmes, however, hepatic gene expression differences were only found in quantitative restriction. Higher counts of Lactobacillus and Clostridium cluster IV groups in ileum are likely to be related to better broiler performance and low expression of lipogenic genes.
Keywords: fast-growing strain; feed restriction programmes; hepatic metabolism; intestinal microbiota